Variação, herdabilidade e ganhos genéticos em progênies de Eucalyptus tereticornis aos 25 anos de idade em Batatais-SP - Macedo, Hugo Rodrigo [UNESP]; Menezes Freitas, Miguel Luiz; Teixeira de Moraes, Mario Luiz [UNESP]; Zanata, Marcelo; Sebben, Alexandre Magno (Ipef-inst Pesquisas Estudos Florestais, 2013)
The wood of Eucalyptus tereticornis is intensively used for timber, structures, buildings, poles, posts and coal. The aim of this study was to estimate genetic parameters and genetic and phenotypic correlations in growth and stem form traits of 52 open-pollinated progenies of E. tereticornis sampled from three Australian populations (20 progenies from Helenvale, 19 from Ravenshoe and 13 from Mt. Garnet). The progenies were compared with three commercial control also from Australian. The experimental design used was the compact family block, with the effect of provenance allocated in the plots and progenies within provenances in the sub-plots. Ten repetitions of the 52 treatments, sub-plots with six plants and the spacing of 3 × 2 m was used. At 25 years of age it was measured the diameter at breast height (DBH), total height, true volume and the stem form. We found genetic variation amon and within the three provenances and the possibility of obtaining high gains from mass selection and individual among and within progenies. The provenance Helenvale showed the best development for DBH, height and volume. The traits DBH, height and volume showed high genetic correlations (> 0.9), indicating the possibility to use the indirect selection. The coefficient of heritability on a progeny mean for the traits DBH and height was median, being 0.31 and 0.30, respectively. The expected genetic gain with the selection were estimated at 12.4% for DBH and 8.5 % for plant height. These results will subsidize the transformation of the provenance and progeny test in a seedling seed orchard and a clonal seed orchard.
Variation, heritability and genetic gain in progeny of Eucalyptus tereticornis at 25 years of age in Batatais-SP
Keywords: Eucalyptus; Genetic parameters; Quatitative traits; Species domestication; Tree breeding